Assessing self–other agreement and dyadic adjustment in marital dyads - Joshua D. Dwire; Marvin W. Acklin (Frontiers in Psychology)
In this study, we examined self–other agreement in married couples to examine the association between their perceptions of self and other psychological problems and dyadic adjustment. We also postulated that dyadic adjustment would moderate self–other agreement ratings on low- and high-visibility traits of psychological problems. Using a cross-informant assessment design, 101 married dyads in three marital groups (non-clinical, transplant, and divorcing dyads) provided reciprocal self and other ratings for psychological problems. Self–other agreement indices were quantified using self–other differences scores and Pearson r, qualifying (Q) correlations. The self–other agreement models yielded significant differences in dyadic adjustment across couple types. Couples that demonstrated moderate to elevated levels of self–other agreement for psychological problems had higher levels of dyadic adjustment. Differences in self–other psychological problem ratings were robust predictors of dyadic maladjustment and poor relational quality. Dyadic adjustment was found to moderate self–other agreement for psychological problems, especially for wives’ appraisals and husbands’ attunement to wives’ low-visibility problems. The findings validate the impact of self–other agreement in models of relationship conflict and adjustment. Wive’s other views tended to have large effect sizes in dyadic adjustment. The study’s limitations and recommendations for future research are also discussed.